On alterity and sexual difference - Fernández Guerrero, Olaya (Logos. Anales del Seminario de Metafísica, 2012)
This paper takes into account the philosophical issue of alterity, enriched by feminist theory and its reflection on sexual difference. There are, at least, three aspects of feminist theory which are related to alterity: on the first hand, the critique on construction of femininity as alterity against masculinity; secondly, and together with feminism of difference, it is interesting to think about physical and symbolic experiences of motherhood, which provide a new model of ‘irreducible alterity’ and new contents for a Care Ethics; third, and considering Ricoeur’s dialectics between idem-identity and ipse-identity, sexual identity can be redefined as a dialogical and dynamic process concerning discursive and performative dimensions.